INDONESIAN STUDENTS' EXPERIENCES IN STUDYING FOREIGN LANGUAGE USING TECHNOLOGY - Widya Andayani; Rika Andriani; Sherina Rizky Amelya; Hesti Isra Ayu Octavia; Marisi Debora (Universitas Bengkulu, 2021)
The existence of technology in education has impact tremendously in learning. This greatly facilitates the experience of students in order not to be monotonous and boring. The usefulness of the media learning app is very accepted by the public because it allows users, especially for Students. Advantages in the use of media applications can add new knowledge to a lesson. To facilitate the learning experience of the student, to learning to speak German can use the app Quizizz. Features. Quizizz is very easy for students to understand and explore a learning material. This research was conducted by interviewing 10 students of education German language ever use the app Quizizz with the aim to see the opinion of the experience of students who learn using the application. Based on the results of this research, many of the students of the educational program of the German language, said that the experience of learning with the application quizizz is very easy to understand the material of the German language and is also very effective in explore and evaluate his understanding.